The chinese legacy hidden by a local last name - Cortez Prudencio, Candy Li (2020)
The author by using the family memory and review of parish archives, reconstructs the story of two of her Chinese ancestors who settled in the late 19th century in the San Luis de Cañete district, Lima, Peru. She relates how the change of name of her ancestors carried out through Christian baptism impacts to her family and her own life.